Biography of Julio Ramón Segura Moneo, municipal archivist of Tudela - Pérez Sánchez, Beatriz (Huarte de San Juan. Geografía e Historia, 2011)
The article aims to present Julio Segura Moneo, municipal archivist of Tudela, in a comprehensive manner. It has been used an important resource of the testimonies of people who knew him in different areas. However, it is intended as a guideline and leader of the history of their city, Tudela (Navarra), both presented and distributed through its source documentary, the municipal archives.
Keywords: Segura Moneo, Julio; municipal archivist; culture; Tudela (Navarra); Municipality of Tudela (Navarra)